Social participation and employment status in Spain: a human capital approach - Caparrós-Ruiz, Antonio (My University, 2019)
The economic literature has found hard evidence on the great significance of general and specific human capital to participate in the labour market, get an employment and have a career success characterised by higher wages and more options of getting an upward labour mobility through promotions or better jobs in other firms. Recently, additional factors integrated in the concept of social participation have emerged as key determinants on the labour market success. These factors consider the components that create benefit from the interactions and cooperation within and among the different groups composing a community. Thus, individuals will invest in social capital whether its benefit overcomes its cost, similar to the investments decisions made with other productive factors such as human capital. This article contributes to the increasing literature about social capital and its economic effects in Spain by analysing some aspects related to the labour market from a micro-econometric approach, which overcomes some drawbacks associated with the analysis of social capital from an aggregated perspective. In particular, this paper analyses to what extent the social participation (considered as a relational good), and other aspects of the social capital, increase the probability of participating in the labour market, taking into account different employment status. To the extent possible, this analysis will be focused from a human capital approach since the social participation’s effect will be examined grouping individuals according to their educational level. Data used corresponds to the Living Condition Survey (INE), and the methodological approach consists in performing discrete choice models to explain the labour market status, including as regressors different measures of social participation.
Keywords: Participación social; Mercado laboral; Economía de la educación; Congresos y conferencias; Social participation; Labour market; Multinomial logit